Kajian Perolehan Hasil Bijih Timah Berdasarkan Ukuran Butir Terhadap Variabel Magnetic Separator Skala Laboratorium - Muhammad Rizki Pratama; Janiar Pitulima; E.P.S.B Taman Tono (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2021)
Industrial-scale Magnetic Separator is used to process tin ore by separating magnetic and nonmagnetic minerals using a belt conveyor speed and splitter opening only one variation. Based on this, this research is intended to obtain a more varied and optimal combination of variable settings in the recovery of tin ore yields. The method used is quantitative data analysis method by obtaining nonmagnetic minerals using a combination of splitter openings and belt conveyor speed based on grain size, calculating the content of tin ore in non-magnetic minerals using the Grain Counting Analysis method and calculating the composition of tin ore recovery. The research was conducted based on grain sizes of 60 mesh, 80 mesh, and 120 mesh using a combination of splitter opening sizes of 0.2 cm, 0.4 cm, and 0.6 cm and using a belt conveyor speed of 27.12 cm/s, 28.15 cm/s, and 28.40 cm/s. The sample used for each grain size is 9,000 grams with repetition for each combination of variables, namely 30 times. The results of this study obtained the highest yield of tin ore at grain size of 80 mesh as much as 1,753.7 grams in 8,920.3 grams of non-magnetic minerals with tin ore grades of 19.66% using a combination of speed 27.12 cm/s and splitter opening 0.2 cm. Based on the results of the study, the tin ore contained in the non-magnetic material processed by the Magnetic Separator, the grain size of 80 mesh is higher than that contained in the grain size of 60 mesh, while the grain size is finer than 80 mesh, the lower the recovery of tin ore contained in the non-magnetic material. Meanwhile, the larger the splitter opening and the speed of the conveyor belt, the higher the nonmagnetic minerals obtained.